Metropolitan Governance in Asia and the Pacific Rim Borders, Challenges, Futures (Springer Singapore, 2018)
This edited collection examines seminal changes and major policy challenges in metropolitan governance in Asia and the Pacific Rim that are being faced by governments (national and sub-national) and their polities. The book builds upon the work of the largest stream at the Urban Affairs Association's (UAA) Annual Conference (Urban Issues in Asia and the Pacific Rim) - specifically, the chapters arose from presentations at the 2016 UAA Annual Conference in San Diego and ensuing discussions and debates. The book is framed by three over-arching narratives: • the increased importance (economic, political and cultural) of the Asian region within strategic discussions of planetary urbanism and the problematisation of the concept of the Asian region as an element of these discussions • the challenges engendered by the rapid pace of development (again, economic, political and cultural) and the endorsement, tacit or otherwise, of developmentalism in many of the polities under consideration • the increased salience of metropolitan and urban areas, vis-à-vis other levels of governance (national; local; supra-national), particularly how it is seen as key in addressing these challenges.